2018
DOI: 10.5194/amt-11-4981-2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MUSICA IASI tropospheric water vapour profiles using theoretical error assessments and comparisons to GRUAN Vaisala RS92 measurements

Abstract: Abstract. Volume mixing ratio water vapour profiles have been retrieved from IASI (Infrared Atmospheric Sounding Interferometer) spectra using the MUSICA (MUlti-platform remote Sensing of Isotopologues for investigating the Cycle of Atmospheric water) processor. The retrievals are done for IASI observations that coincide with Vaisala RS92 radiosonde measurements performed in the framework of the GCOS (Global Climate Observing System) Reference Upper-Air Network (GRUAN) in three different climate zones: the tro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…Atmospheric temperature is also fitted but constrained strongly to the EUMETSAT IASI Level 2 temperature product. For more details on the MUSICA IASI retrievals and the validation of the MUSICA IASI H2O product please refer to Schneider et al (2016) and Borger et al (2018). The version presented here is an update as described by Borger et al (2018) using a priori profiles for the gases under consideration, which depend on season and latitude.…”
Section: Musica Iasi Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atmospheric temperature is also fitted but constrained strongly to the EUMETSAT IASI Level 2 temperature product. For more details on the MUSICA IASI retrievals and the validation of the MUSICA IASI H2O product please refer to Schneider et al (2016) and Borger et al (2018). The version presented here is an update as described by Borger et al (2018) using a priori profiles for the gases under consideration, which depend on season and latitude.…”
Section: Musica Iasi Productsmentioning
confidence: 99%
“…The overall column sensitivities of TCCON increase with increasing altitude, while the column sensitivities of COCCON decrease with increasing altitude. The AVKs for IASI and TROPOMI are not shown here but can be found in Borger et al, 2018 andSchneider et al, 2020, respectively. https://doi.org/10.5194/amt-2020-378 Preprint.…”
Section: Comparison Between Coccon and Co-located Ground-based Ftir Imentioning
confidence: 99%
See 1 more Smart Citation
“…The MUSICA IASI data full retrieval product encompasses trace gas profiles of H 2 O, the HDO/H 2 O ratio, N 2 O, CH 4 , and HNO 3 . The data have been validated in several previous studies (Schneider et al, 2016;Borger et al, 2018;García et al, 2018), and it has been shown that the CH 4 product can very well detect the CH 4 signals originating in the upper troposphere/lower stratosphere. MUSICA IASI data using processor versions 3.2.1 and 3.3.0 are currently available for the 2014 to 2020 time period and are presented in Schneider et al (2021).…”
Section: A Posteriori Combination Of Musica Iasi Ch 4 and Tropomi Xchmentioning
confidence: 65%
“…Conversely, independent ground-based remote sensing instruments and in situ sensors do not give access to the global scale, but they can provide very accurate and long-term data that can be used for satellite validation. Many studies have investigated water vapor comparisons among satellite and ground-based instruments (Schneider and Hase, 2011;Dupuy et al, 2016;Borger et al, 2018;Trieu et al, 2019), but there are only few studies that focus on the Arctic region (Pałm et al, 2010;Buehler et al, 2012;Alraddawi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%